A case report of hepatopulmonary syndrome in hereditary hemorrhagic telangiectasia (HHT): Not all right-to-left shunting in HHT is due to pulmonary arteriovenous malformations. Issue 32 (August 2018) - Krishnan, Sheila; Lahm, Tim
Abstract: Rationale: Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant disorder characterized by abnormal vessel growth that results in telangiectasias and arteriovenous malformations (AVMs) in the skin, mucosa, and viscera. Up to 30% of patients with HHT exhibit pulmonary AVMs (PAVMs), clinically manifesting as right-to-left shunting and hypoxemia. Patient Concerns: We report an unusual and novel case of a patient with HHT who lacked clinical sequelae of portal hypertension but presented to clinic with hypoxemia without dyspnea. Diagnoses: Diagnostic workup revealed noncardiac right-to-left shunting due to hepatopulmonary syndrome (HPS) from HHT-induced portal hypertension rather than PAVMs. The diagnosis was confirmed by the absence of PAVMs on chest computed tomography and evidence of elevated portal pressures as noted by the presence of small esophageal varices on upper endoscopy and histologic findings on liver biopsy. Intervention: Due to the patient's mild symptoms, no further intervention was required. He was closely followed up in the outpatient setting for changes in symptoms and underwent annual screening for development of PAVMs. Outcomes: The patient continues to do well clinically. He has not experienced worsening hypoxemia or dyspnea and has not developed PAVMs. Lessons: Given that management of hypoxemia in HPS drastically differs from that of hypoxemia due to PAVMs, this case demonstrates the importance of evaluating HHT patients for HPS if they exhibit impaired oxygenation and noncardiac right-to-leftshunting in the setting of hepatic arteriovenous shunting.